(untitled) (Experimental biology, 2015)
Screening of 26 samples of winter rape on content of nutritional and anti-nutritional compounds was done. Content of oil varied between 42.7 -47.1%, protein –from 3.6 to 24%, content of erucic acid in oil of analyzed set changed from 0.8 to 29.6,level of glucosinolates: from 0.6 to 2.75%.